Evaluasi Pemeriksaan Magnetic Resonance Elastography Untuk Menentukan Fibrosis Hati Dengan Metode Counturing Confidence MAP - Clara Ulisia Simatupang; Mahfud edy Widiatmoko; Nurul Rosita Indrianti (Jurnal Imejing Diagnostik (JImeD), 2026)
Background: Magnetic Resonance Elastography (MRE) is a non-invasive liver imaging technique used to assess tissue stiffness by measuring liver stiffness values expressed in kilopascals (kPa). In relation to which, this research was undertaken to describe the technical aspects of hepatic MRE examination and to analyse the distribution of fibrosis stages based on kPa values obtained from the upper, middle, and lower regions of the liver. Methods: This research employed a qualitative method with descriptive design. Risearch under taken at Radiology Medistra Hospital Jakarta. The data collection methods employed were observation, interviews, and document review. The study participants consisted of two radiographers and one radiologist, each with more than three years of experience in MRE examinations. Results: ROI measurement results for the liver are clearly displayed, including the conversion values ​​to stiffness (Table 1). The MRE technique produces a color-coded elastogram designed to assist physicians in their interpretation (Table 4). The contouring confidence map method was shown to improve the reliability of ROI selection by ensuring that measurement areas were located within regions of good elastogram quality. This approach yielded reliable mean liver stiffness values, which were subsequently classified into fibrosis stages and analysed as the percentages. Conclusions: Magnetic Resonance Elastography (MRE) using the contouring confidence map method provides accurate and representative evaluation of hepatic tissue stiffness.